Сучасний стан пенсійного страхування в Україні - Мельник, Т. А.; Коцюрба, О. Ю.; Melnyk, T.; Kotsiurba, O. (ЦНТУ, 2023)
Сучасний стан пенсійного страхування в Україні постійно вимагає додаткових досліджень, які би актуалізували показники його розвитку, виявляли би нові тенденції його розвитку, обґрунтовували би доцільність його реформування, врахували би вплив різних факторів. Мета дослідження полягає у тому, що на основі проведеної оцінки сучасного стану системи пенсійного страхування в Україні виявити головні її проблеми розвитку та обґрунтувати практичні рекомендації щодо напрямів реформування соціальної політики держави стосовно пенсійного забезпечення. The current state of pension insurance in Ukraine constantly requires additional research that would update its development indicators, reveal new trends in its development, justify the feasibility of its reform, and take into account the influence of various factors. The purpose of the study is that based on the assessment of the current state of the pension insurance system in Ukraine, it is necessary to identify the main problems of its development and substantiate practical recommendations on the directions of reforming the social policy of the state regarding pension provision. The compulsory state pension insurance indicators in Ukraine, conducted by the Pension Fund of Ukraine for 2018-2022, were evaluated, which revealed the main trends of development and outlined the main problems. The performance indicators dynamics of non-state pension funds in Ukraine over the past five years has been investigated, trends in the development of accumulative non-state pension insurance have been outlined. The life insurance market in Ukraine is investigated and the voluntary pension insurance indicators are analyzed separately, which provides for the achievement by the insured person of the retirement age determined by the contract. The bank deposits dynamics of households in Ukraine as the potential of additional pension provision of the population is considered.
The current state of pension insurance in Ukraine
Keywords: Пенсійний фонд України; недержавний пенсійній фонд; страхування додаткових пенсій; Pension Fund of Ukraine; non-state pension fund; additional pensions insurance